Pressure injury associated with mechanical restraint: a cross-sectional study (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objective: To verify the association of the practice of mechanical restraint with pressure injury (PI) in hospitalized patients. Method: A cross-sectional study of 111 patients from medical, surgical and intensive care units at a public hospital in the state of Rio de Janeiro, Brazil. To analyze the association between variables, the [odds ratio (OR)] was adopted. Results: It was found 57 patients in mechanical restraint (51.4%). In the group of patients contained, the occurrence of PI was estimated at 43.9% and in the group of patients not contained in 5.6%. The chance of the contained patient to present PI was 13 times higher than in patients not contained. The location of the injury was more frequently in the sacral region, classified as stage 2 (21.1%) and stage 3 (12.3%), followed by trochanter (15.8%) and calcaneus (10.5%). Conclusion: It is recommended the adoption of nursing practices of suppression or reduction of the time in the use of mechanical restraint, adopting educational measures and prevention of PI.
Keywords: Stomatherapy; Pressure ulcer; Physical restraint.Study of Manufacturing Processes for Liquid Rocket Turbopump Impellers; Test and Analysis